Thermoluminescence yield of neutron irradiated Gd:Mg-Doped silica glass - N.T., Abahreh; Sani, S.F. A.; Ismail, S.S.; Fernando, Laura Elizabeht; Tamchek, N.; Julia, A. K.; Almugren, K.S.; Nur Adilah, Roslan; A.S, Siti Shafiqah; Bradley, D.A. * (Elsevier, 2023)
The thermoluminescence yield of silica glass doped with Gd2O3 and MgO is investigated as a potential material for neutron dose measurement. The dosimetric materials used herein were prepared via the sol-gel route with concentration of rare earth metal oxides varying from 1 to 10 mol%. Reactor irradiations were made at 750 kW thermal power, producing thermal, epi-thermal and fast neutron fluxes of 5.61 × 1012, 2.51 × 1012, 2.58 × 1012 n/cm